2020
DOI: 10.1111/jog.14546
|View full text |Cite
|
Sign up to set email alerts
|

Is Valsalva maneuver an alternative to use tenaculum for endometrial sampling procedure in cases where the cervix cannot be passed spontaneously with pipelle? A randomized study

Abstract: Aim To evaluate the effect of the Valsalva maneuver on ease of the endometrial sampling procedure in cases where the cervix cannot be passed spontaneously. Methods A randomized prospective trial was conducted in 84 patients whose cervix could not pass spontaneously with pipelle, and they were randomized for the Valsalva maneuver or tenaculum groups. In 43 of a total of 84 patients, we requested Valsalva maneuver throughout the process to pass the cervical canal, and in 41 patients, we performed tenaculum to pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Pretrial data have suggested a 30.0% insertion failure rate among control patients. Pilot data with the Valsalva maneuver from Narin et al 14 suggest that the relative risk (RR) of failure in patients in the experimental group in relation to those in the control group was 0.447. Assuming that a full bladder has the same efficacy as the Valsalva maneuver and applying an a of 0.05 and power of 80.0%, we needed 96 participants in each arm to detect a 20.0% difference between groups for Pipelle insertion failure rate (https://openepi.com/ SampleSize/SSCohort.htm).…”
Section: Methodsmentioning
confidence: 99%
“…Pretrial data have suggested a 30.0% insertion failure rate among control patients. Pilot data with the Valsalva maneuver from Narin et al 14 suggest that the relative risk (RR) of failure in patients in the experimental group in relation to those in the control group was 0.447. Assuming that a full bladder has the same efficacy as the Valsalva maneuver and applying an a of 0.05 and power of 80.0%, we needed 96 participants in each arm to detect a 20.0% difference between groups for Pipelle insertion failure rate (https://openepi.com/ SampleSize/SSCohort.htm).…”
Section: Methodsmentioning
confidence: 99%